مكانة وجهود الحافظ ابن حجر العسقلاني رحمه الله في علم العلل: Status and Contributions of Ibn Hajar al-‘Asqalani in The Science of ʿIlal (Hidden Defects in Hadith) - Maulana La Eda (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2026)
This study examined the scholarly status and contributions of Ibn Hajar al-Asqalani in the science of ʿilal (hidden defects in hadith), one of the most intricate and challenging disciplines of hadith studies. The research aimed to highlight his position among hadith critics and to analyze his methodological approach in identifying subtle defects through an inductive and analytical study of his works and teaching sessions. The study demonstrated that Ibn Hajar served as a bridge between early and later scholars, adhering to the methodology of leading critics such as al-Bukhari and al-Daraqutni, while refining, explaining, and weighing their opinions. His engagement with ʿilal is evident in both theoretical and applied works, particularly in Fath al-Bari and al-Nukat ʿala Ibn al-Salah. The research concluded that Ibn Hajar is among the foremost later scholars who significantly preserved and advanced the science of ʿilal.